Catasetum sophiae, a new species of Orchidaceae (Catasetinae) from northern Brazil - Valsko, Jefferson José; Krahl, Amauri Herbert; Petini-Benelli, Adarilda; Chiron, Guy (Phytotaxa, 2019)
A new taxon, native to the shores of the Curiquidi pond, in the State of Amazonas, is described and illustrated. In the shape of the labellum, it is similar to Catasetum callosum and to C. transversicallosum. However, as far as the antennae are considered, C. sophiae is more similar to C. yavitaense. Placed in the section Isoceras with convergent antennae, C. sophiae can be distinguished to all the members of this group by its labellum mainly characterised by its saccate portion with margin entire or sparsely ciliated, and particularly by its glabrous frontal lobe furnished with a laterally compressed table-shaped callus projected forward. Besides, the frontal lobe is elongated in C. yavitaense and short and truncate in C. sophiae.